Sri Lanka : Environmental Iissues in the Power Sector - World Bank (Washington, DC, 2013)
This paper describes the study undertaken to assist the government of Sri Lanka in identifying a path toward sustainable power development. The timing of the report is important, as Sri Lanka is about to embark on the development of coal-fired power plants over the coming years. The purpose of this study is to determine how much cheaper coal-fired generation is than other energy sources; how much more environmentally friendly are the alternatives; what impacts would be more environmentally friendly; and what effect would the policies have on power sector costs and electricity tariffs. The report seeks to provide a quantitative analysis that will help decision-makers assess various power sector policy options in terms of the trade-offs between environment, costs, and other impacts. The study makes recommendations only if options are unambiguously winwin; but more often than not, tradeoffs are required, and ultimately the government must decide what it considers to be more important. A number of alternative policies and technologies were systematically analysed, and the report gives a brief description of each option.